Juridification and judgement calls: Swedish schoolteachers’ reflections on dealing with bullying, harassment, and degrading treatment - Paul Horton; Camilla Forsberg; Robert Thornberg (Education Inquiry)
While teachers are obliged to report and investigate incidents of bullying, harassment, and degrading treatment in Swedish schools, research suggests that they sometimes struggle to decide which incidents to report. In this study, we investigate Swedish schoolteachers’ reflections on dealing with bullying, harassment, and degrading treatment, and on balancing their pedagogical work with juridical demands to report. The study is based on qualitative interviews conducted with teachers at three comprehensive schools in Sweden, which were analysed in relation to Bronfenbrenner’s social-ecological framework. The findings demonstrate that teachers make judgement calls regarding which incidents to report and that these influence and are influenced by micro-, meso-, exo-, macro- and chronosystem factors. The findings also suggest that increasing demands for professional accountability negatively affect the professional responsibility of teachers and may lead to them making judgement calls that are not always in the best interests of the children for whom they have responsibility.